Professional Self-Efficacy of Primary School Teachers In the Conditions of the New Ukrainian School - Zhigaylo , Oksana; Petrovska, Karyna (Educological discourse, 2023)
The article examines the peculiarities of the work of a teacher of primary classes of the New Ukrainian School through the prism of a personal construct. It has the analysis of literary sources on the selected problem done. We can also see that the impact of the level of professional self-efficacy of primary school teachers on professional activity and its results has been studied, which is important for understanding the characteristics of a teacher’s work. It is shown the identified manifestations of self-efficacy in different spheres of life, which contribute to the identification of professional self-efficacy, that directly affects the professional activity of a teacher. It indicates the compared and analysed number of functions of the teacher, highlighted in the Professional Standard, which require careful work and confidence in a positive result, which directly depends on the teacher’s self-efficacy. We can also investigate the experienced connection between the results of previous studies and the established requirements built not only on professional skills, but also on personal constructs that are part of the teacher’s personality. It informs about the analysed results of research in the field of professional self-efficacy of teachers and the described features of performing functions through the prism of professional self-efficacy. It says it has been proven that a teacher with high self-efficacy can evaluate not only his work results without any fear, but also carry out a qualitative analysis of the work of others, provide a reasoned constructive assessment of others and their work. A teacher who is not afraid of difficulties on the way to the goal, flexible when solving tasks, critical and fair to his activity and the work of others, will not be afraid to hear or give feedback in the circle of the work team.